The development of an automated irrigation system using an open source microcontroller - Hassan, Aslinda; Md Shah, Wahidah; Harum, Norharyati; Bahaman, Nazrulazhar; Mansourkiaie, F. (Universiti Teknikal Malaysia Melaka (UTeM), 2019)
This paper proposes an automated irrigation using Arduino microcontroller system which is cost effective and can be used in a farm or in an average home garden. The proposed system is developed to be automatically watering the plants when the soil moisture sensor detected water insufficiency in the soil by using the Arduino as the center core. The automated irrigation system is a fully functional prototype which consists of a soil moisture sensor; an LCD display to show the moisture percentage and pump status; a relay module which is used to control the on and off switch of the water pump; and a water pump. When the soil moisture sensor senses the dry soil, it will show the moisture percentage on the LCD display, and the relay module will switch on the water pump automatically to start the watering process or vice versa. Hardware testing is conducted to ensure the proposed system is fully functional.